2020
DOI: 10.1111/saje.12260
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Monetary and Macroprudential Policies for the South African Economy

Abstract: We investigate the optimal design and effectiveness of monetary and macroprudential policies in promoting macroeconomic (price) and financial stability for the South African economy. We develop a New Keynesian dynamic stochastic general equilibrium model featuring a housing market, a banking sector and the role of macroprudential and monetary policies. Based on the parameter estimates from the estimation, we conduct an optimal rule analysis and an efficient policy frontier analysis, and compare the dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…On the one hand, controlling house prices is one of the main roles of macroprudential policies. From a real estate market perspective, macroprudential policies can effectively combat housing demand shock (Turdaliev & Zhang, 2019), monetary policy shocks (Alpanda & Zubairy, 2017), interest rate shocks (Mendicino & Punzi, 2014), credit shock (Liu & Molise, 2020) and technology shocks (Rubio & Comunale, 2017), effectively curbing house price volatility. On the other hand, the appreciation of housing assets has become the absolute source for wealth development of Chinese residents; housing is both consumer goods and investment assets.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…On the one hand, controlling house prices is one of the main roles of macroprudential policies. From a real estate market perspective, macroprudential policies can effectively combat housing demand shock (Turdaliev & Zhang, 2019), monetary policy shocks (Alpanda & Zubairy, 2017), interest rate shocks (Mendicino & Punzi, 2014), credit shock (Liu & Molise, 2020) and technology shocks (Rubio & Comunale, 2017), effectively curbing house price volatility. On the other hand, the appreciation of housing assets has become the absolute source for wealth development of Chinese residents; housing is both consumer goods and investment assets.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…There is near consensus that the 2007/2008 global financial crisis emanated from real estate booms and busts. Accordingly, many studies focus on the effects of macroprudential tools on the housing sector (Angelini, Neri, & Panetta, 2014; Brzoza‐Brzezina et al, 2015; Lambertini et al, 2013; Liu & Molise, 2020; Mendicino & Punzi, 2014; Quint and Rabanal, 2014; Ravn, 2016; Rubio and Carrasco‐Gallego, 2014; Rubio & Yao, 2020). These studies investigate the key elements of the real estate sector, namely, the LTV ratio that serves as a macroprudential tool to improve financial stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This stabilisation has added benefits when monetary policy interacts with macroprudential policy. Liu and Molise (2020) establish that within a general equilibrium framework featuring heterogeneous borrowers from distinct sectors, combining monetary and macroprudential policies promotes financial and macroeconomic stability, especially when monetary policy does not react to financial conditions. In contrast, Funke et al (2018) found that the coordination of the two policies causes financial and macroeconomic instability.…”
Section: Introductionmentioning
confidence: 99%
“…We investigate how management risk perception, also known as risk taking behavior, has a significant impact on policy transmission while exacerbating procyclicality with in financial system (Satria and Juhro, 2011). We also capture two forms of macro-financial linkages that explain real-financial linkages through banking sector ownership of government securities and risky portfolios (Liu and Molise, 2020). Both linkages are explicitly modeled to capture procyclical behavior in the financial sector and how it will affect the dynamics of the aggregate demand.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to include since changes in financial regulation and monetary policy have an impact on the effectiveness of policy transmission. Although capital regulation aims to promote financial stability by increasing risk absorption capacity, it also creates friction and magnifies procyclicality (Meh and Moran, 2010;Angeloni and Faia, 2013;Rubio and Carrasco-Gallego, 2016;Liu and Molise, 2020). Naiborhu (2020) empirically shows that higher capital buffers moderate the impact of monetary policy on credit growth.…”
Section: Introductionmentioning
confidence: 99%